2020
DOI: 10.3390/molecules25122752
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and In Vitro Sustained Release Profile of Resveratrol-Loaded Silica Aerogel

Abstract: Silica aerogel, a kind of nanoporous material, is regarded as a desired drug carrier for its low toxicity, high specific surface area, and excellent biocompatibility. Using silica aerogel in a drug carrier may be an appropriate method to improve the performance of pure resveratrol. In this study, resveratrol-loaded silica aerogel (RSA) as a drug delivery system was prepared by the sol-gel method. Before gelling, resveratrol was added into the hydrolyzed tetraethyl orthosilicate (TEOS) ethanol solution then dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…One of the possibilities to provide appropriate concentrations of these substances at sites of the damaged joints, and in particular in the cartilage, is the use of specific biomaterials such as silica aerogel. Indeed, it has been shown that resveratrol-loaded silica aerogel is biocompatible and stable, and that when it is coupled with the anti-inflammatory effects of resveratrol, it showed good potential for osteoarthritis treatment [ 30 ]. Based on our results, Belinal is a strong candidate to be tested with the same strategy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possibilities to provide appropriate concentrations of these substances at sites of the damaged joints, and in particular in the cartilage, is the use of specific biomaterials such as silica aerogel. Indeed, it has been shown that resveratrol-loaded silica aerogel is biocompatible and stable, and that when it is coupled with the anti-inflammatory effects of resveratrol, it showed good potential for osteoarthritis treatment [ 30 ]. Based on our results, Belinal is a strong candidate to be tested with the same strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dusty feature of silica aerogel particles can particularly produce a dry sensation in the skin and irritation by friction. [88][89][90][91][92][93][94][95][96][97] 99 Sol-gel and supercritical drying/SA: 470 to 750 m 2 g −1…”
Section: Cytocompatibility Of Silica Aerogelsmentioning
confidence: 99%
“…Environmental Science: Nano Critical review Silica aerogels and hybrid aerogels containing silica have been tested regarding cytocompatibility with several cell lines (adipose tissue, fibroblasts, blood, neurons, osteoblasts, keratinocytes, endothelial cells, chondrocytes, tumour cells). 91,93,95,[97][98][99][100][101][102][103] In general, silica-based aerogels presented good cytocompatibility with cell viabilities above 90% (Table 3) and have been even proposed as scaffolds to promote cell growth and proliferation for the ultimate goal of tissue growth or as artificial heart valve leaflets. [94][95][96]98,102,104 Silica aerogels have been also proposed as a non-cytotoxic and safe carrier or vector of different drugs (resveratrol, 5-fluorouracil, paclitaxel, methotrexate) for local and systemic administrations.…”
Section: Mammal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled release of loaded antibacterial materials is essential. It has been reported that drug release is limited by the skeletal structure of the aerogel; such that the release rate decreases with the prolongation of release time [ 83 ]. Wang et al [ 84 ] reported that the change in the ratio of ingredients of the precursor materials would result in the aerogels with ordered pore structures and stable properties.…”
Section: Biopolymer-based Aerogels For Antibacterial Deliverymentioning
confidence: 99%